Analysis Of The Budget Realization Report (Lra) At The Sub-District Office Of Seberang Musi Kepahiang District - Nella Indra Dewi Sijabat; Neri Susanti; Nenden Restu Hidayah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
The purpose of the study was to analyze the level of effectiveness of PAD revenue and the efficiency of the Budget Realization Report (LRA) expenditure budget in financial performance in 2021-2022 at the Head Office of Seberang Musi Sub-District, Kepahiang Regency. This type of research uses quantitative data and qualitative data, the operationalization of research uses ratio variables in analyzing the Budget Realization Report at the Head Office of Seberang Musi Sub-District, Kepahiang Regency, there are two ratios, namely the effectiveness ratio and the efficiency ratio. The method used is descriptive quantitative using effectiveness and efficiency ratios. The results of the research conducted show that the performance of PAD revenue is ineffective with a percentage, namely in 2021 of 0% and in 2022 of 0% and the Expenditure Budget is less efficient with a percentage in 2021 of 98.32% and in 2022 of 94.46.